Web-based Inventory Information System using Agile Scrum Method at CV Tunggal Putra Jaya - Widaningsih, Nona; Windiyanti, Noni; Rukhviyanti, Novi (Sistemasi: Jurnal Sistem Informasi, 2025)
CV Tunggal Putra Jaya is a building materials store that still manages inventory manually using Microsoft Excel. This approach leads to data inaccuracies, difficulties in real-time stock monitoring, and risks of overstocking or stock shortages. This research aims to design a web-based inventory system to address these issues, with key features such as real-time stock monitoring, order and pre-order creation, and automatic financial report generation. The system is developed using the Agile Scrum method with a sprint duration of 14 days to ensure flexibility to changes in requirements. The implementation results show an efficiency increase of up to 92.73%, marked by a reduction in invoice creation time from 5–10 minutes to 1 minute, stock monitoring from 30 minutes to 1 minute, and financial report generation from 10 minutes to 1 minute. The system has also successfully passed Black Box testing for all features, and user validation indicates that this system can significantly reduce working time.